SISTEM BERBASIS WEB DALAM MENDUKUNG PROSES MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA - Yanuarti, Elly; Irawan, Devi; Wahyuningsih, Delpiah; Perkasa, Eza Budi; Pambudi, Dita Heru (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The Village Development Planning Meeting (Musrenbangdes) is one of the annual activities carried out by Pagarawan Village. The current system has not yet digitized the administrative process of implementing musrengbangdes. The submission of activity proposals by community members is still done manually using handwriting on a piece of paper. All processes are still paper-based, making them less effective and efficient. In the current era, web technology should be utilized to improve services to the community. This research will develop a web-based system to accelerate the process of village development planning administration services. The analysis and design method used is object oriented method with UML diagram tools. The system development method uses Rapid Application Development (RAD). The results of system testing are 100% valid so that this system is declared feasible to implement. This web-based system was developed in accordance with the needs and provides easy access for the community in Pagarawan Village, accelerates the process of processing data for village development planning meetings (musrenbangdes), data is stored properly and neatly and makes it easier to search for data and information.